Phenotypic and Genotypic Detection of Virulence Factors Affecting Proteus mirabilis Clinical Isolates - Fawad Hayat; Muddasir Khan; Muhammad Umair; Sajeela Akbar; Rida Javed; Syed Hussain Shah (Current Trends in OMICS, 2023)
The current study attempts the phenotypic and molecular detection of the virulence factors of Proteus mirabilis clinical isolates. A total of 600 urine samples were collected from urinary tract-infected patients at Khyber Teaching Hospital, Peshawar, Pakistan. P. mirabilis isolates were identified through different biochemical tests. Virulence factors including urease production, biofilm formation, and swarming phenomenon were determined by using different markers (ureC1, rsbA, and luxS genes), identified via the polymerase chain reaction (PCR) technique. Out of the selected samples, 95 samples (15.83%) were identified as P. mirabilis. The molecular study showed that all isolates (100%) possessed the ureC gene. Whereas, 90.52% and 92.63% of the isolates gave positive results for biofilm formation (rsbA gene) and swarming phenomenon (luxS gene), respectively. The phenotypic and molecular study of P. mirabilis virulence factors provides a better understanding of how P. mirabilis infection spreads. The results could be used for prevention and improvements in its clinical treatment.